2013
DOI: 10.4102/curationis.v36i1.59
|View full text |Cite
|
Sign up to set email alerts
|

Minibus taxi drivers’ sexual beliefs and practices associated with HIV infection and AIDS in KwaZulu- Natal, South Africa

Abstract: Risky sexual behaviours in South Africa are a major contributing factor to the spread of HIV infection and AIDS. HIV infection amongst minibus taxi drivers is a concern, because these people belong to an occupational group that exhibits risky behaviours due to the demands of their work. Given the high vulnerability of minibus taxi drivers, exploring the sexual beliefs and health-related sexual practices of this group will assist in planning targeted interventions. The objectives of this study were to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Ncama et al . ( 2013 ) confirmed that the taxi industry forms the backbone of the public transport industry and accounts for the bigger chunk of daily public commuting. It is therefore important to ensure that taxi drivers remain healthy to the benefit of themselves and their passengers.…”
Section: Introductionmentioning
confidence: 93%
“…Ncama et al . ( 2013 ) confirmed that the taxi industry forms the backbone of the public transport industry and accounts for the bigger chunk of daily public commuting. It is therefore important to ensure that taxi drivers remain healthy to the benefit of themselves and their passengers.…”
Section: Introductionmentioning
confidence: 93%
“…Usually, sex workers and truck drivers are regarded as the highest risk for STI and HIV transmission and minibus taxi drivers are reported as another important vulnerable category [20, 21]. HIV infection amongst minibus taxi drivers is a concern, because of the occupational demand of being away from their families for long times and in some cases being exposed to unhealthy environment and falling prey to unhealthy sexual practices [21]. Minibus taxi drivers are identified as a high-risk population group with an increased risk of HIV infection because the minibus industry is characterized by a high level of migration, low level of education and stressful working conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Minibus taxi drivers are identified as a high-risk population group with an increased risk of HIV infection because the minibus industry is characterized by a high level of migration, low level of education and stressful working conditions. Moreover, the focus of existing research has been on the assessment of HIV infection and AIDS in the transport industry amongst truck drivers, but not in the minibus industry in Gauteng province and in, South Africa generally [21]. Men in the transport industry have high sexual risk behaviors and low HIV risk perceptions, which have implications for STI transmission [21, 22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations